Sport startups new advances in entrepreneurship - Ratten, Vanessa (Emerald Publishing Limited, 2020)
Sport Startups: New Advances in Entrepreneurship examines the global growth of startup enterprises in the sports sector and addresses how they contribute to new developments in business innovation and entrepreneurship. Highlighting the unique challenges faced by startups in this sector, Vanessa Ratten explores approaches to business model development, branding and marketing, and the utilization of new technologies to build successful enterprises, underpinning her study with a clear theoretical framework rooted in institutional theory. Sport Startups is one of the first books to specifically focus on the role of startups in sport. Analyzing the inherent start-up aspect of the sporting sector, due to the combination of profit and non-profit ties, which means that many sport enterprises are developed as new start-up business ventures as they link in with the community. The book foregrounds how startups in sport are vital in developing a better global society that emphasizes the role of health and fitness in communities. Sport Startups will be illuminating reading for all scholars of innovation, entrepreneurship, sports management and business studies.